Pola Pemanfaatan Lahan Di Kawasan Keselamatan Operasi Penerbangan (KKOP) Bandar Udara Sultan Hasanuddin, Makassar - Nini Apriani Rumata (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2020)
Makassar City is the gateway to Eastern Indonesia. This then encouraged the development of the city of Makassar from various fields, causing the inevitable growth of residential settlements. This research was conducted with the aim of being able to map the level of land use in the area around the airport in accordance with the Aviation Operations Safety standard at Sultan Hasanuddin International Airport. This goal is achieved by using descriptive qualitative analysis and buffer analysis with GIS software. The result of this research is mapping the area according to the area analysis that has been carried out using the method described earlier and providing recommendations for land use around the airport